A randomized controlled trial of Kundalini yoga in mild cognitive impairment. (16th January 2017) - Eyre, Harris A.; Siddarth, Prabha; Acevedo, Bianca; Van Dyk, Kathleen; Paholpak, Pattharee; Ercoli, Linda; St. Cyr, Natalie; Yang, Hongyu; Khalsa, Dharma S.; Lavretsky, Helen
ABSTRACT: Background: Global population aging will result in increasing rates of cognitive decline and dementia. Thus, effective, low-cost, and low side-effect interventions for the treatment and prevention of cognitive decline are urgently needed. Our study is the first to investigate the effects of Kundalini yoga (KY) training on mild cognitive impairment (MCI). Methods: Older participants (≥55 years of age) with MCI were randomized to either a 12-week KY intervention or memory enhancement training (MET; gold-standard, active control). Cognitive (i.e. memory and executive functioning) and mood (i.e. depression, apathy, and resilience) assessments were administered at baseline, 12 weeks and 24 weeks. Results: At baseline, 81 participants had no significant baseline group differences in clinical or demographic characteristics. At 12 weeks and 24 weeks, both KY and MET groups showed significant improvement in memory; however, only KY showed significant improvement in executive functioning. Only the KY group showed significant improvement in depressive symptoms and resilience at week 12. Conclusion: KY group showed short- and long-term improvements in executive functioning as compared to MET, and broader effects on depressed mood and resilience. This observation should be confirmed in future clinical trials of yoga intervention for treatment and prevention of cognitive decline (NCT01983930).